Olive growing in Herzegovina - Biško, Ante (Array, 2019)
The cultivation of olive trees (Olea europaea L.) has been expanding in Herzegovina significantly in the last fifteen years. In the past olives were principally grown in the hinterland of Neum, while in recent years the olive groves have been spreading throughout other parts of Herzegovina, in particular in the vicinity of the town of Ljubuški. Most common are the small family plantations. However, in some cases, there are plantations of several to 50 hectares. In the past fifteen years approximately 300 hectares of olive groves were planted. Unfortunately, in some cases, not enough attention was paid to the selection of sites in terms of appropriate soil- and microecological conditions, and to the selection of pollinators. The most common variety is Oblica, autochthonous Croatian variety, characterized by good tolerance to poor and shallow soil, drought and low temperatures. Oblica is followed by Istarska bjelica, Leccino and Pendolino, which together make up about 90% of varieties. Less commonly grown varieties include Carolea, Levantinka and Buža (approximately 10% of varieties). Several autochthonous Croatian varieties and some introduced varieties are being used as pollinators. Levantinka (that is commonly used as Oblica’s pollinator in Croatia) proved to be sensitive to frost in Herzegovina, so it should be used only to a limited extend in appropriate sites, or it should be omitted. The situation is similar with the variety Pendolino which showed, compared to the Oblica, more sensitive to frost, and the growers have to be cautious if planning to use it as a pollinator.